2018
DOI: 10.22159/ijpps.2018v10i2.22018
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Service Quality and Patient Satisfaction at Pharmacy Department in Yogyakarta, Indonesia

Abstract: Objective: To measure the gap between patients' expectations and perceptions about services delivered in the pharmacy department. Methods:A questionnaire concerning the perceived quality of health care sent to out-patients in the pharmacy department, in a government hospital in Sleman district, Yogyakarta Province, Indonesia, during a period of 2016. Participants were two hundred patients aged 18 or older responded to the survey and provided their own ratings of the care. The SERVQUAL model was employed, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This is because the patients' expectation is higher than their perception. Similar results are shown in a study conducted in Yogyakarta that reported negative gap scores in all dimensions of pharmaceutical care services [20]. The lowest gap scores for primary-level health facilities are on drug information and patient counseling and monitoring, whereas the lowest gap scores for secondary-level health facilities are on prescription screening and waiting time.…”
supporting
confidence: 86%
“…This is because the patients' expectation is higher than their perception. Similar results are shown in a study conducted in Yogyakarta that reported negative gap scores in all dimensions of pharmaceutical care services [20]. The lowest gap scores for primary-level health facilities are on drug information and patient counseling and monitoring, whereas the lowest gap scores for secondary-level health facilities are on prescription screening and waiting time.…”
supporting
confidence: 86%
“…That could be also the reason for patient dissatisfaction with the price of medication. This is also the case with other studies done in Pakistan where free or lower cost medication increased patient satisfaction [15].Unlike the present study, different studies showed that age, gender, marital status, level of education were associated with clients' satisfaction [15,29,30]. The difference might be in part due to difference in studied facilities.…”
Section: Discussionsupporting
confidence: 61%
“…Treatment experiences turn to be frustrating when faced with unexpected treatment cost, the occurrence of side effects from medication, confusing drug information, inconvenient pharmacy hours, lack of social/emotional support, unfriendly health-care professionals, difficult payment/reimbursement, and long wait times. Furthermore, patients' satisfaction as seen by the patient is critically important in formulating efficient to health-care delivery systems [27]. Hence, patientcentrism [28] becomes a core concept in the health-care industry, and in such a philosophy, doctors play a significant role.…”
Section: Observations From Previous Studiesmentioning
confidence: 99%